Performance of Lecturers in Preventing Learning Loss Hypotension - Sarma Panggabean; Pontas Jamaluddin Sitorus; Ernawati Br Surbakti (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the refunctional performance of lecturers in preventing hypotensive learning loss in Indonesian language and literature education study program students. This research is a type of qualitative research. The sample of this research comes from students of the Indonesian language and literature education study program. Data collection techniques are interviews and documentation. Data analysis consists of data reduction, data presentation, and drawing a conclusion. The results of this study conclude that the potential learning loss that arises is characterized by the loss of interaction between lecturers and students (86%) and interaction between students and students (80%) and students cannot concentrate (60%) and other factors (40%). The survey results stated that lecturers experienced work stress when facing changes in the learning process from face-to-face (offline) to online (online).